On the system of mood in European and Brazilian Portuguese - Marques, Rui (2022)
This paper is concerned with mood distribution in European and Brazilian Portuguese. Although, in many cases, these two varieties do not differ as regards the selected mood, there are exceptions in some contexts. The variations involve rather different constructions, at first sight suggesting a chaotic picture. However, if one assumes that mood is associated with the expression of an attitude towards a proposition (in other words, that mood is an expression of modality), it becomes clear that European and Brazilian Portuguese are diverging in respect to the relevant factors for mood selection. In particular, while in European Portuguese the selection of mood is sensitive to both veridicality and epistemic modality, Brazilian Portuguese is becoming a language where the truth-value of the proposition is the main factor responsible for mood selection. Hence, a tendency appears to be developing for Brazilian Portuguese to approach the pattern found in languages like Rumanian, (Modern) Greek or Hungarian, while European Portuguese follows the pattern found in most other Romance languages.